The Latest Green Synthesis of Silver Nanoparticles Using Cocoa Fruit Peel Extract (Theobroma cacao L.) as a Bioreductant - S. Kasim; W. Riskiyani; A.N. Zahra; I W. Sutapa; A. Kamari; C. Baskar (International Journal of Acta Material, 2025)
Cocoa fruit peel contains a variety of phytochemicals, including tannins, flavonoids, alkaloids, terpenoids, and saponins, which are anticipated to act as reducing agents. The green synthesis method employs methanol as a solvent to extract organic compounds from cocoa fruit peel, which serve as bio-reductants. This study aims to synthesize silver nanoparticles utilizing cocoa fruit peel extract as a bio-reductant. It involved the preparation of silver nitrate (AgNO₃) solutions at varying concentrations of 0.5 mM, 1 mM, and 1.5 mM. Characterization of the nanoparticles was conducted using a UV-Vis spectrophotometer and a Particle Size Analyzer (PSA). The study observed the formation of silver nanoparticle colloids after 30 minutes of stirring, as evidenced by a color change in the colloid to brown. UV-Vis spectrophotometer analysis revealed a maximum wavelength of 461 nm with an absorbance value of 2.032. Notably, as the concentration of silver nitrate (AgNO₃) increased, the absorbance value correspondingly increased. The PSA results indicated that the silver nanoparticles had an average size of 96.08 nm.